Effects of chronic core training on serum and erythrocyte oxidative stress parameters in amputee football players - Kurtoğlu, Ahmet; Konar, Nurettin; Akçınar, Faruk; Çar, Bekir; Üremiş, Nuray; Türköz, Yusuf; Eken, Özgür; Ceylan, Halil İbrahim and Knappova, Vera and Barasinska, Magdalena and Gabrys, Tomasz (Frontiers in Physiology, 2023)
Objective: The positive impact of aerobic exercise on blood oxidative stress parameters is well documented. However, the effect of core exercises on these parameters in amputee football players (AF) remains unclear. Therefore, this study aims to investigate the impact of core exercises on blood oxidative stress parameters in this population. Methods: Experimental method was adopted in the study. Eleven elite AF players participated in the study. The participants were divided randomly into two groups a core exercise group (CEG) and a control group (CG). Blood measurements were taken before and after the 8-week core exercise program. Blood measurements included erythrocyte Total Oxidant Status (eTOS), erythrocyte Total Antioxidant Status (eTAS), erythrocyte oxidative stress index (eOSI), serum nitric oxide (sNO), serum Total Oxidant Status (sTOS), serum Total Antioxidant Status (sTAS), serum oxidative stress index (sOSI), serum total thiol (sTT), serum native thiol (sNT), and serum disulfide (sDS) parameters were studied. Results: According to the results of the study, a significant difference was found between the 0th and eighth week pre-aerobic training load (ATL) sTOS (p = .028) values of CEG values. A significant difference was found in sTOS (p = .028) and sOSI (p = .028) values after the 0th and eighth-week pre-ATL. A significant difference was found in the sTOS (p = .043) and sOSI values (p = .043) of CG at week 0th and eighth-week pre-ATL. Conclusion: Overall, the results suggest that core exercises had a positive effect on blood oxidative stress parameters in AF players by reducing blood total oxidant levels.